2012
DOI: 10.1242/jeb.065540
|View full text |Cite
|
Sign up to set email alerts
|

Polarotactic tabanids find striped patterns with brightness and/or polarization modulation least attractive: an advantage of zebra stripes

Abstract: SUMMARYThe characteristic striped appearance of zebras has provoked much speculation about its function and why the pattern has evolved, but experimental evidence is scarce. Here, we demonstrate that a zebra-striped horse model attracts far fewer horseflies (tabanids) than either homogeneous black, brown, grey or white equivalents. Such biting flies are prevalent across Africa and have considerable fitness impact on potential mammalian hosts. Besides brightness, one of the likely mechanisms underlying this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
115
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(131 citation statements)
references
References 35 publications
12
115
1
3
Order By: Relevance
“…While the association between striping and warm humid months might imply stripes being a means of reducing heat load, this seems unlikely, given the lack of association with any maximum temperature in any multivariate model. Instead, our results lend strong ecological and comparative support to experiments that show that some tsetse and tabanid species avoid black and white striped surfaces [11][12][13][14] . Biting flies are attracted to hosts by odour, temperature, vision and movement that may act at different stages during host seeking, but vision is thought to be important in the landing response 27 with dark colours being particularly attractive 28 .…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…While the association between striping and warm humid months might imply stripes being a means of reducing heat load, this seems unlikely, given the lack of association with any maximum temperature in any multivariate model. Instead, our results lend strong ecological and comparative support to experiments that show that some tsetse and tabanid species avoid black and white striped surfaces [11][12][13][14] . Biting flies are attracted to hosts by odour, temperature, vision and movement that may act at different stages during host seeking, but vision is thought to be important in the landing response 27 with dark colours being particularly attractive 28 .…”
Section: Discussionsupporting
confidence: 76%
“…It is therefore noteworthy that stripes on all parts of the body except the forehead lie perpendicular to the outline of the zebra's body. Egri et al 14 showed that tabanids are less likely to land on black and white striped surfaces than uniform black or (arguably) white surfaces, that this effect is more marked as stripe width declines and that the most effective deterrent stripe widths used in their experiments matched the range of stripe widths found on the three species of zebra. From the literature, we recalculated glossinid, tabanid and stomoxys preferences for varying stripe widths.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Alternatively, given that zebra live in herds, the stripes could serve both a background matching and disruptive function, if the background is considered to be other zebras. Ironically, given their frequent occurrence in discussions on camouflage, the only function for zebra stripes that has been experimentally tested is their effectiveness in repelling biting flies (Waage 1981;Egri et al 2012).…”
Section: Concealing Motionmentioning
confidence: 99%
“…Females of many tabanid species have to find a host animal to obtain a blood meal that ensures egg development. The host choice of these tabanids is partly governed by the linear polarization of light reflected from the host's coat (Horváth et al 2010b;Egri et al 2012). This polarization-based, i.e.…”
Section: Introductionmentioning
confidence: 99%